Prevalence of psychiatric diagnosis and related psychopathological symptoms among patients with COVID-19 during the second wave of the pandemic - Zhiyang Zhang; Yi Feng; Rui Song; Di Yang; Xuefei Duan (BMC, 2021)
Abstract Background The possibility of psychopathological symptoms and related risk factors among normal persons and patients infected during the outbreak of COVID-19 has been widely investigated. The mental health outcomes of the second wave of the pandemic remain unclear, especially those of patients with an infection. Thus, this study aims to explore the prevalence of and related risk factors associated with psychopathological symptoms among patients infected with COVID-19 during the second wave. Method A cross-sectional survey was conducted in five isolated wards of a designated hospital in Beijing, China, from July 1 to July 15, 2020. The Mini International Neuropsychiatric Interview (MINI) was conducted to assess psychiatric disorders, and a series of scales were used to measure self-reported psychopathological symptoms and psychosomatic factors. Multivariate regression analysis was used to analyze the risk factors associated with psychopathological symptoms. Results Among 119 participants with infections, the prevalence of generalized anxiety symptoms (51.3%), depressive symptoms (41.2%), and posttraumatic stress symptoms (PTSS)/posttraumatic stress disorder (PTSD) symptoms (33.6%) was observed. Loneliness, hope, coping strategies, and history of mental disorders were the shared risk or protective factors across several psychopathological symptoms. The perceived impact of COVID-19 is the specific risk factor associated with state anxiety symptoms. Conclusions The prevalence of symptoms of depression, anxiety, and PTSS/PTSD is high among patients with infections during the second wave of the pandemic in Beijing. Clinical doctors must realize that these patients will probably experience depressive disorder, anxiety disorders, and PTSS/PTSD, as well as some neuropsychiatric syndromes. Specific mental health care is urgently required to help patients manage the virus during the second wave of the pandemic.